Photocaging of Pyridinylimidazole-Based Covalent JNK3 Inhibitors Affords Spatiotemporal Control of the Binding Affinity in Live Cells - Beate Sandra Hoffelner; Stanislav Andreev; Nicole Plank; Pierre Koch (MDPI AG, 2023)
The concept of photocaging represents a promising approach to acquire spatiotemporal control over molecular bioactivity. To apply this strategy to pyridinylimidazole-based covalent JNK3 inhibitors, we used acrylamido-N-(4-((4-(4-(4-fluorophenyl)-1-methyl-2-(methylthio)-1H-imidazol-5-yl)pyridin-2-yl)amino)phenyl)benzamide (1) as a lead compound to design novel covalent inhibitors of JNK3 by modifying the amide bond moiety in the linker. The newly synthesized inhibitors demonstrated IC50 values in the low double-digit nanomolar range in a radiometric kinase assay. They were further characterized in a NanoBRETTM intracellular JNK3 assay, where covalent engagement of the target enzyme was confirmed by compound washout experiments and a loss in binding affinity for a newly generated JNK3(C154A)-NLuc mutant. The most potent compound of the series, N-(3-acrylamidophenyl)-4-((4-(4-(4-fluorophenyl)-1-methyl-2-(methylthio)-1H-imidazol-5-yl)pyridin-2-yl)amino)benzamide (13), was equipped with a photolabile protecting group leading to a nearly 10-fold decrease in intracellular JNK3 binding affinity, which was fully recovered by UV irradiation at a wavelength of 365 nm within 8 min. Our results highlight that photocaged covalent inhibitors can serve as a pharmacological tool to control JNK3 activity in live cells with light.